2012
DOI: 10.5874/jfsr.18.403
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Willingness to Buy Biodiversity-Friendly Agricultural Products

Abstract: The aim of this paper is to clarify the determinants of consumer willingness to buy biodiversityfriendly agricultural products. To this end, this study considers a Japanese case: fish-friendly rice that targets the preservation of habitat for the indigenous fish of Lake Biwa in Shiga Prefecture. We cast a spotlight on consumer characteristics identified from market segmentation based on consumer awareness and behavior and, in addition, ex ante consumer knowledge about the rice. The willingness to buy is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Whether the respondents have experience in farming, and whether they have strong feelings toward Higashiosaka City are not statistically significant in this case. The notable finding is that respondents with lower-income tend to obtain more economic rewards than those with higher income do, although many previous studies revealed that higher-income households are more likely to choose organic or environment-friendly products (Davies et al, 1995;Nishimura et al, 2012). This result indicates that the economic rewards of the FBP are incentives for purchase, motivating lower-income households to purchase locally certified products, and to collect labels to get more rewards.…”
Section: Characteristics Of Consumers Who Repeatedly Purchase Locallymentioning
confidence: 90%
See 1 more Smart Citation
“…Whether the respondents have experience in farming, and whether they have strong feelings toward Higashiosaka City are not statistically significant in this case. The notable finding is that respondents with lower-income tend to obtain more economic rewards than those with higher income do, although many previous studies revealed that higher-income households are more likely to choose organic or environment-friendly products (Davies et al, 1995;Nishimura et al, 2012). This result indicates that the economic rewards of the FBP are incentives for purchase, motivating lower-income households to purchase locally certified products, and to collect labels to get more rewards.…”
Section: Characteristics Of Consumers Who Repeatedly Purchase Locallymentioning
confidence: 90%
“…In terms of social and demographic factors, many studies showed that female consumers are more likely to purchase such products (Byrne et al, 1992;Davies et al, 1995;Nishimura et al, 2012;Cholette et al, 2013). Consumers who have children living in the household (Thompson and Kidwell, 1998) and those who are older (Cicia et al, 2002;Brown, 2003) tend to purchase value-added products.…”
Section: Conceptual Frameworkmentioning
confidence: 99%